How Irrigation Level and Soil Type Affect Nutritional Quality and Yield of Greenhouse Tomato Grown Under Mild Environmental Conditions - Eleni Papoui; Anna Gkotzamani; Konstantinos Nikoloudis; Filippos Bantis; Athanasios Koukounaras (Horticulturae, 2025)
Cherry tomato is a highly demanding crop regarding temperature and water requirements. Considering that the climate crisis has already affected soil quality, water quality and quantity, and temperatures throughout the year, some cultivation practices may need to adapt to the new reality. This research aims to investigate whether soil type in a greenhouse (Zones 1 and 2), deficient irrigation (50% of the optimal irrigation according to the producer), or their interaction can affect the fruit production per plant and quality of cherry tomatoes. Evaluated parameters included total and monthly fruit production per plant, phenolic compounds, antioxidant activity, total soluble solids, and lycopene content. Results indicate that fruit production per plant was not significantly affected by any treatment or their interaction. Cherry tomato fruit quality was not dramatically affected by either soil type or irrigation level. To conclude, irrigation levels can be reduced by 50% without compromising tomato fruit quality and production per plant. These results can be a potential to adaptation to the climate crisis and water scarcity.